High specificity of MMSE pentagon scoring for diagnosis of prodromal dementia with Lewy bodies. Issue 3 (March 2015) - Cagnin, Annachiara; Bussè, Cinzia; Jelcic, Nela; Gnoato, Francesca; Mitolo, Micaela; Caffarra, Paolo
Abstract: Background: Patients with dementia with Lewy bodies (DLB) may display a different cognitive pattern from Alzheimer's disease (AD) with more severe impairment performing visuospatial/visuoconstructive tasks. The aim of this study was to investigate whether the analysis of the MMSE pentagon copy could be a useful diagnostic screening tool in prodromal DLB. Methods: Fifty-three patients with Mild Cognitive Impairment (MCI) were followed over 3-years until a diagnosis of DLB (MCI–DLB: n  = 30) and AD (MCI–AD: n  = 23) were made according to standard criteria. At the first assessment patients underwent a thorough cognitive assessment including the Qualitative Scoring MMSE Pentagon Test (QSPT), the NPI, the UPDRS as well as questionnaires to determine fluctuations and sleep disorders. Results: The percentage of subjects who were unable to determine the correct number of angles in the pentagon copy test was 45.1% of MCI–DLB and 8.3% of MCI–AD patients (sensitivity 41.1%; specificity 91%). Attentive/executive functions and visual-spatial abilities were worse in the MCI–DLB group, while episodic memory impairment was greater in MCI–AD. Subtle extrapyramidal signs (63%) and RBD symptoms (56%) were the most frequent clinical features supporting the diagnosis of MCI–DLB. Conclusions: We suggest that a poor performance in determining the number of angles when performing the pentagon copying test, together with the presence of subtle extrapyramidal signs and symptoms of RBD may serve as a predictive tool for early DLB. Highlights: MMSE pentagon copy was studied as screening tool in prodromal DLB. Wrong pentagon's number of angles was detected in 45.1% of MCI–DLB. SE 41.1% and SP 91% in discriminating between DLB and AD at the MCI stage.